الإعْجَازُ التشرِيْعِي فِي القُرْآنِ الكريمِ ضوَابِطُهُ ونمَاذجُهُ - Ridha, Ismu (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2021)
The Qur'an has various forms of miracles, one of which is al-i'jaz at-tasyri'i (miracles of Islamic law). Therefore, this study will highlight how the miracles of the Shari'a are, the measuring standards along with examples that are appropriate and not in accordance with these rules. This type of research is a qualitative research where the researcher focuses on library data sources as the main resource. Then the data is described by descriptive analysis and analyzed critically (content analysis) and then gives a conclusion.The results of the study indicate that there are five criteria or rules that must be met. First, to distinguish between i'jaz tasyri'i and taujih ijaz (an attempt to explain the miraculous side) where the miracle of the Shari'a is something that is certain, while the taujih has the possibility of being right or wrong. Second, that the Shari'a contained in the Qur'an is something that is beyond the reach of the power of human reason. Third, I'jaz tasyri'i is contained in one discussion theme and not in the scope of one verse or one surah alone. Fourth, it must be underlined that not all the wisdom and secrets of His shari'a miracles can be revealed in real terms. Fifth, do not violate the rules and rules of interpretation in the analysis.